INTERPRETATION OF THE VERSES OF THE QUR'AN ABOUT THE NATURE OF SCIENCE - Zannatunnisya Zannatunnisya; Imran Ariadin; Hamzah Hamzah (Proceeding International Seminar of Islamic Studies, 2022)
The enlightenment obtained by Muslims namely on scientific thinking that refers to the Qur'an and Hadith. The awareness of Muslim scientists to develop knowledge according to what is taught by the Qur'an and Hadith. As for this paper, it explains the nature of science according to the Qur'an by using interpretation, so that the greatest knowledge is achieved. Characteristics taught by The Koran that must have an open mind, and allow gaining knowledge. The purpose of this article is to build understanding of the Qur'an with analysis to mainly about knowledge. This article was written based on a literature review on related knowledge and the interpretation of the Qur'an is part of Islamic epistemological knowledge.This article is expected to be a filter in anticipating the negative effects of the development of science and technology.Keywords: Interpretation, Verses, The Qur'an, Nature